Academic publishing career paths — initial research and observations - CARDEN, Mark (Learned Publishing, 2015)
ABSTRACT The job titles and career paths of people transitioning between academia and scholarly publishing, and of those who are progressing within their publishing careers, has been little studied and lacks accepted frameworks, ‘route‐maps’, and taxonomies. Much of the work done to date provides merely a ‘snapshot’ of the current demographics of the publishing workforce at particular moment, and tends not to offer insight into pathways, trajectories, or momentum. This preliminary survey, involving around 150 scholarly publishers, reveals insights into job titles, progressions, and transitions, and exposes some of the reasons for transitions between academia and publishing. The analysis suggests that these transitions and career paths can be systematically studied and documented, for use both by individuals considering their own careers, and by planners and managers in academic institutions and scholarly publishing organizations.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA4Ny8yMDE1MDMwNA